2022
DOI: 10.1186/s12913-022-08707-7
|View full text |Cite
|
Sign up to set email alerts
|

Cost of hospital services in India: a multi-site study to inform provider payment rates and Health Technology Assessment

Abstract: The 'Cost of Health Services in India (CHSI)' is the first large scale multi-site facility costing study to incorporate evidence from a national sample of both private and public sectors at different levels of the health system in India. This paper provides an overview of the extent of heterogeneity in costs caused by various supply-side factors.A total of 38 public (11 tertiary care and 27 secondary care) and 16 private hospitals were sampled from 11 states of India. From the sampled facilities, a total of 32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…8 An Indian study identified that hospital bed size, annual number of hospital admissions and level of care predominantly predicted the unit cost of hospitalisation at the district hospital level. 42 Consistent with these findings, our study found that the number of beds, ALOS, annual number of hospital admissions and teaching status of hospitals were significantly associated with heterogeneity in unit costs per bed-day hospitalisation while controlling for state-level variations Open access financing and system characteristics. In theory, the cost gradients generated from the regression analysis can be used for weighting where there is sufficient justification for differential reimbursement.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…8 An Indian study identified that hospital bed size, annual number of hospital admissions and level of care predominantly predicted the unit cost of hospitalisation at the district hospital level. 42 Consistent with these findings, our study found that the number of beds, ALOS, annual number of hospital admissions and teaching status of hospitals were significantly associated with heterogeneity in unit costs per bed-day hospitalisation while controlling for state-level variations Open access financing and system characteristics. In theory, the cost gradients generated from the regression analysis can be used for weighting where there is sufficient justification for differential reimbursement.…”
Section: Discussionsupporting
confidence: 84%
“…Further, a global multicountry study found that ownership of hospitals, teaching status of hospitals, GDP of country, ALOS, bed occupancy rate and number of admissions were significant predictors of cost per bed-day hospitalisation 8. An Indian study identified that hospital bed size, annual number of hospital admissions and level of care predominantly predicted the unit cost of hospitalisation at the district hospital level 42…”
Section: Discussionmentioning
confidence: 99%
“…Unit costs of health system visit was also added for each bleeding event. For severe bleeding events, additional costs (as mentioned earlier in prophylactic emicizumab costs) were added [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, supply-side factors associated with unit costs include provider type (private vs public, district vs tertiary), the scale of activity (size of the facility or number of patients), geography (rural vs urban or metro city vs non-metro), input prices (salaries and prices of consumables and equipment) and the input mix (skill level of human resources, the ratio of staff to beds) 16–18. The CHSI study provided an assessment of heterogeneity in healthcare costs attributable to supply-side factors 19. One of the findings of the assessment revealed significant differences in adjusted bed day costs when comparing hospitals located in tier 3 cities with those in tier 1 and tier 2 cities (tier 1 cities are those with the highest cost of living, tier 3 are those with the lowest) and adjusted procedure costs when comparing tier 2 and tier 3 cities.…”
Section: Cost Evidence For Rate-setting In Pm-jaymentioning
confidence: 99%